An examination of PTSD symptoms and their effects on suicidal ideation and behavior in non-treatment seeking veterans. (April 2019) - Law, Keyne C.; Allan, Nicholas P.; Kolnogorova, Kateryna; Stecker, Tracy
Highlights: The effect of PTSD symptoms on suicidal ideation and suicidal behavior in veterans who are not currently seeking mental health treatment was examined. A bifactor solution comprising a general PTSD factor and specific symptom clusters out performed a correlated factors solution. General PTSD alone predicted suicidal ideation one month later while general PTSD and re-experiencing symptoms both predicted suicidal behavior one month later. Abstract: This study sought to examine the effect of general PTSD symptoms as well as specific PTSD symptom clusters on suicidal ideation and suicidal attempts. We first compared a correlated factors solution consistent with the DSM- 5 symptom clusters for PTSD with a bifactor solution comprising a General PTSD factor and orthogonal specific factors. Using the best fitting model (i.e., bifactor solution), we then investigated the effect of specific PTSD symptom clusters on severity of suicidal ideation and suicide attempts above and beyond the effect of general PTSD symptoms. A sample of 773 veterans who have never sought professional mental health treatment were screened for suicidal ideation within the past two weeks. One month after the baseline measurement, the participants completed a follow-up assessment, again by telephone. A bi-factor solution was used to account for a general PTSD factor as well as the specific DSM-5 PTSD symptom clusters. After controlling for baseline suicidal ideation and behavior, it appeared that the Anxious Arousal factor was predictive of changes in the magnitude of severity of suicidal ideation and the General PTSD factor was predictive of the onset of new suicidal behavior at the one-month follow-up. Additionally, the Re-experiencing factor of PTSD also significantly predicted new suicidal behavior at the one-month follow-up. These results suggest that it may beneficial for clinicians, who are assessing individuals with PTSD for suicidality, to be aware of the frequency, duration, and content of their clients' repetitive, intrusive thoughts as these thoughts may increase their capability to inflict non-lethal or lethal forms of self-injury.